OPTIMALISASI UMKM MADU LIAR DI DESA MANGUNAN, DLINGO, BANTUL DIY - Yessi Jusman; Renda Sukma Tamara; Nurul Kurnia Sukmawati; Pinkan Adhisa Nurulia; Gigih Ashabul Kahfi (LPPM Universitas Abdurrab, 2022)
The University of Muhammadiyah Yogyakarta Real Work Lecture (KKN) activity during this pandemic used a new scheme, based on Information Technology, because it was still facing the Covid-19 pandemic situation. Implementation of real work lectures based on Information Technology (IT), the 019 KKN IT UMY group chose the Micro, Small and Medium Enterprises (UMKM) of Pak Sulaiman's Original Honey in Mangunan Village as partners in implementing the work program compiled by the 019 KKN IT UMY group. The target of the Real Work Lecture service activity in Mangunan Village, Dlingo District, Bantul Regency. This activity is related to partner, Wild Bee Honey UMKM, in Mangunan Village. With the main target of this KKN activity is to develop the Wild Bee Honey UMKM to be more developed in the process of production, presentation, and product marketing.